Expression of autophagy related genes in peripheral blood cells in Parkinson's disease. (25th September 2021) - Tu, Hai-Yue; Gu, Yong-Quan; Li, Xia; Pei, Shao-Fang; Hu, Li-Fang; Wang, Ya-Li
Highlights: This study aimed to investigate whether the rhythm of autophagy is altered in PD. BECN1 and LAMP2 levels were decreased in patients with PD. The rhythm of autophagy in PD is not consistent with that in the Control group. Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder and affects dopaminergic neurons. Autophagy often shows a circadian rhythm pattern under physiological conditions across 24 h. Abnormal autophagy and circadian dysfunction are two characteristics of PD. Whether the rhythm of autophagy is altered in PD has not yet been reported. Therefore, in this study, we collected peripheral blood samples at 6:00 h and 18:00 h from PD patients and age-matched controls, and analyzed the mRNA expressions of ULK1, BECN1, LAMP2, AMPK, and SNCA using real-time quantitative PCR. Blood samples analysis found that BECN1 and LAMP2 levels were decreased in patients with PD. Simultaneously, the rhythm of autophagy in PD is not consistent with that in the Control group, which may be a manifestation of the abnormal biological rhythm of PD.